2003
DOI: 10.1021/ol034320+
|View full text |Cite
|
Sign up to set email alerts
|

Sonogashira Coupling Reaction with Diminished Homocoupling

Abstract: [reaction: see text] The side product from homocoupling reaction of two terminal acetylenes in the Sonogashira reaction can be reduced to about 2% using an atmosphere of hydrogen gas diluted with nitrogen or argon. Terminal arylethynes, diarylethynes, and a few new arylpyridylethynes with donor substituents have been synthesized in very good yields. Comparative control experiments suggest that the homocoupling yield is determined by concentration of both catalyst and oxygen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
164
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(167 citation statements)
references
References 27 publications
3
164
0
Order By: Relevance
“…10 Replacing PPh 3 with P(Oi-Pr) 3 gives similar results with aldehydes, but shows better reactivities towards ketones and greatly facilitates the purification step.…”
Section: Recent Improvementsmentioning
confidence: 95%
See 2 more Smart Citations
“…10 Replacing PPh 3 with P(Oi-Pr) 3 gives similar results with aldehydes, but shows better reactivities towards ketones and greatly facilitates the purification step.…”
Section: Recent Improvementsmentioning
confidence: 95%
“…The homologation itself is slower (24 h at 0-10 1C), but if performing the reaction at higher temperatures (40-50 1C) diminishes the reaction time, it also leads to a loss of enantiopurity. In a typical experiment, 26 (340 mol%) and K 2 CO 3 (350 mol%) are added at 0 1C on a solution of 22 (340 mol%) in CHCl 3 . After 48 h in an ice-bath, a second portion of K 2 CO 3 (160 mol%) is added, followed by a solution of the aldehyde (100 mol%) in MeOH and the reaction is stirred at the same temperature for 24 h.…”
Section: Scheme 21mentioning
confidence: 99%
See 1 more Smart Citation
“…[256] Two equivalents of TMS-acetylene were used in this procedure, presumably due to the expected copper mediated Glaser-Hay homodimerisation side reaction, which usually occurs upon incomplete exclusion of oxygen. [257] However, despite only obtaining 17 % isolated yield of the TMS-acetylene homodimer, none of the desired product was obtained. The use of Et 3 N base as the solvent for the reaction with gentle heating at 50 °C (entry 2) resulted in precipitation of a thick black solid, potentially containing the catalytically inactive palladium black, and resulting in a poor mass recovery.…”
Section: Figure 116mentioning
confidence: 99%
“…The formation of 2 was first observed when attempts were made OPEN ACCESS M840 (Page 2) to react TEB with sterically demanding 2-substituted aryl halides in Sonogashira-type reactions (crosscoupling by copper halides and organic-based Pd catalysts) [22]. Homocoupling of terminal acetylenes is a well-known side reaction under such conditions and the dimerization has been shown to involve oxidation of copper acetylides formed in-situ [5,7,[23][24][25][26][27][28][29][30]. Further investigations aiming at obtaining 2 in high yield revealed that dimerization of TEB occurred in the absence of a palladium catalyst as well, and the reaction was particularly successful and furnished the dimer in high yield when TEB was reacted with an amine, e.g., triethylamine, in the presence of copper(I) iodide and air.…”
mentioning
confidence: 99%